1986
DOI: 10.1210/jcem-62-6-1155
|View full text |Cite
|
Sign up to set email alerts
|

Type I Diabetes is Characterized by Insulin Resistance Not Only with Regard to Glucose, but also to Lipid and Aminoacid Metabolism*

Abstract: Resistance to the metabolic effects of insulin has been reported with regard to glucose disposal in type I diabetic patients (IDDM) even when they were euglycemic. Our aim was to study glucose, lipid, and amino acid metabolism during glucose clamping at multiple levels of insulin in 10 normal (N) and 6 IDDM patients. Blood glucose was maintained constant (4.7 mmol/liter) at three insulin plateaus (160 min each) [42 +/- 6 (SD) 89 +/- 11, and 1255 +/- 185 microU/ml in N and 36 +/- 4, 80 +/- 13, and 1249 +/- 107 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…In accordance with the results of previous reports [31,33], we found that the plasma levels of lactate and pyruvate increased during the hyperinsulinaemic, euglycaemic clamp, indicating an enhanced rate of the overall nonoxidative glucose utilization. While several recent studies [3][4][5] suggest that adipose tissue in humans may be an important source of lactate production in vivo, it is not possible from the present findings to estimate the contribution of lactate derived from subcutaneous fat, since the kinetic pattern of lactate (and pyruvate) in the adipose tissue extracellular space was indistinguishable from that in arterial blood.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the results of previous reports [31,33], we found that the plasma levels of lactate and pyruvate increased during the hyperinsulinaemic, euglycaemic clamp, indicating an enhanced rate of the overall nonoxidative glucose utilization. While several recent studies [3][4][5] suggest that adipose tissue in humans may be an important source of lactate production in vivo, it is not possible from the present findings to estimate the contribution of lactate derived from subcutaneous fat, since the kinetic pattern of lactate (and pyruvate) in the adipose tissue extracellular space was indistinguishable from that in arterial blood.…”
Section: Discussionsupporting
confidence: 93%
“…In diabetic patients, hypoglycaemia is mainly associated with absolute hyperinsulinaemia which causes inhibition of ketogenesis and low blood ketone concentrations. In contrast, blood lactate concentration tends to be high in insulin-treated diabetic patients [18], and becomes even higher under conditions of relative hyperinsulinaemia as it occurs, for instance, in the situation of increased physical activity [19] and inadequate insulin dose adjustment.…”
Section: Discussionmentioning
confidence: 97%
“…Blood was collected into EDTA tubes and rapidly centrifuged at 4°C. The plasma was then stored at -20°C (18). Plasma free fatty acid concentrations were determined by an enzymatic method (19).…”
Section: Methodsmentioning
confidence: 99%